Morfological Variation of Endemic Fish Rainbow Celebensis (Telmatherina celebensis Boulenger) in Lake Towuti, South Sulawesi - S.H. Nasution; . Sulistiono; D.S. Sjafei; G.S. Haryani (Jurnal Akuakultur Indonesia)
Rainbow Celebensis (Telmatherina celebensis Boulenger) is one of endemic fish is a part of richness of biodiversity and world heritage in Lake Towuti. Rainbow Celebensis have beautiful colour especially in male, so that it is an economically and potentially as ornamental freshwater fish. It should be protected from threats because to fear decrease offish population in nature. This research is to know morphological variation of endemic fish rainbow Celebensis based on standard morphometric character in several stations. This research is conducted in Lake Towuti, South Sulawesi from March 2002 until April 2003 in four stations were I: Bakara Cape, II: inlet of Lake Towuti for River Tominanga, III: Loeha Island, IV: outlet of Lake Towuti to River Hola-hola. Sample were collected using experimental gillnet sized of 3A, 1, lA, and VA inch. Measuring offish standard morphometric character to be down on Kottelat et al. (1993) with modification covering 14 characters. The result of univariate and multivariate analysis towards standard morphometric character, could be said that male and female at I, II, III, and IV station is same tendency or to be deacended from one fish population. The characteristic to have influence of male are body hight and length from mouth to first pectoral fin, whereas in female are forskal length, total length, and basic length of second pectoral fin.